Characterization and risk factors for pressure ulcers in the hospitalized elderly - Chrystiany Plácido de Brito Vieira; Mirtes Sousa Sá; Maria Zélia de Araújo Madeira; Maria Helena Barros Araújo Luz (Universidade Federal do Ceará, 2014)
This study aimed to identify the socio-demographic and clinical characteristics; obtain the risk factors for pressure ulcers identified in hospitalized senior citizens. This is a prospective, descriptive, and quantitative study. The sample consisted of 215 hospitalized elderly people in a public hospital in Teresina, PI, Brazil, in orthopedic, neurological, medical, and surgical clinics, and Intensive Care Units from November/2012 to February/2013. Data collection happened through interviews, physical examinations, and medical records. The average age was 71.8 years old, most patients were female (55.3%), with low education, and married. The majority were taken into orthopedics (42.3%). For the length of hospital stay, the average was of 12.4 days. The most prevalent risk factors were hypertension, use of analgesics, antihypertensives, and anticoagulants. Eighty-seven senior citizens (40.5%) presented low risk. One highlights the importance of nursing care in the prevention and assessment of risk for pressure ulcers in order to reduce its incidence in hospitals.